Comunidades de bactérias e árqueas e produção de biogás em célula experimental de resíduos sólidos urbanos - Aires, Kellianny Oliveira (2018)
Populations of bacteria and archaea are responsible both for the degradation of Urban Solid Waste (USW) and for the production of biogas present in landfills. However, the knowledge of these microorganisms in solid grounded waste can lead to the development of more efficient technological alternatives for the biodegradation process and the biogas production, with a positive impact on the operation of landfills, public health and the environment. In this sense, the objective of this work was to investigate the communities of bacteria and archaea and the production of biogas in urban solid wastes grounded in an experimental Cell. The methodology used in this work included the construction stage, statistical planning of the neighborhoods of Campina Grande-PB for collection and filling of the experimental Cell with USW. Samples residues were collected monthly for DNA extraction by the methods Kit and CTAB, amplification was performed with universal and specific primers of the 16S region the products were analyzed by PCR and DGGE, subsequently, the samples were quantified purified and sent for sequencing. The physico-chemical and microbiological indicators of USW monitored in situ and in the laboratory were: temperature, humidity, pH, volatile solids and quantification of total aerobic microorganisms. The biogas produced in the experimental Cell was measured by means of a portable infrared detector that measured the concentrations of CH4, CO2, O2, CO e H2S. The results showed that the main bacteria found were Uncultured Pseudomonas sp, Uncultured bacterium, Enterobacter sp., Klebsiella pneumoniae, Uncultured Bacillus sp. which participated in the hydrolysis, acidogenic and acetogenesis processes. Amongst the archaea species have been characterized Methanosarcina flavescens, Methanosarcina mazei, Methanosarcina spelaei and Methanosaeta concilii indicating that the acetoclastic methanogenesis was the predominant pathway for synthesis of methane in the biodegradation of USW. The analysis of the microbiological and physico-chemical indicators was favorable to the biodegradation of the residues, to the development of microbial communities and to the production of biogas. The experimental Cell feedback process, with new residues, increased to the amount of organic matter, however, CO2 concentrations exceeded those of CH4, which had a maximum value of 20%.